ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP PERTUMBUHAN LABA PADA BANK UMUM SYARIAH DI INDONESIA - Zhanalia Fitrianisa (2021)
This study aims to analyze financial performance factors using the variables of Capital, Liquidity and Operational Efficiency on Profit Growth for Islamic Commercial Banks (BUS) registered with the Financial Services Authority (OJK) for the period 2015 to 2019. The data used in this study are secondary data with The sample collection method uses Saturated Sampling. Thus, the population and sample are the same, namely 14 Islamic Commercial Banks. Data analysis in this study was conducted using Microsoft Office Excel 2013, and hypothesis testing using panel data regression analysis with the E-Views version 10.0 program with a significance level of 5%. The results of the research are (1) Capital (Capital Adequacy Ratio) has a negative effect on Profit Growth, (2) Liquidity (Financing Debt to Ratio) has a positive effect on Profit Growth, (3) Operational Efficiency (Operational Expense Operational Revenues) has a negative effect on Profit Growth.